A Secure Wireless Information and Energy Cooperation Transmission Strategy in Spectrum Sharing Networks With Untrusted Dual-Relay - Daqian Zhao; Hui Tian; Ping Zhang (IEEE Access, 2019)
Spectrum efficiency, energy efficiency, and physical layer security are three critical issues in designing wireless networks, such as an energy-constrained device-to-device (D2D) communication in secure spectrum sharing femtocell networks. In this paper, we investigate a problem of security cooperation transmission between a single-antenna primary system and a multi-antenna wireless-powered untrusted secondary system, where the untrusted secondary devices can be regarded as potential malicious decoders. A novel artificial noise-aided (AN-aided) joint time division- and power splitting-based three-phase secure wireless information and energy cooperation transmission strategy is proposed for spectrum sharing networks with untrusted cooperative dual-relay. Furthermore, we consider two scenarios that the untrusted secondary system knows perfect and imperfect channel state information (CSI). We focus on the design of time division ratios, power splitting ratios, and beamforming vectors, with the objective to maximize the data rate of the untrusted secondary system, subject to the target data rate requirement of the primary system and the untrusted secondary system's confidentiality constraints, energy harvesting requirements, and power consumption constraints. Simulation results demonstrate that our proposed strategy is the best and significantly improves the average data rate of the untrusted secondary system under different primary user target data rate requirements, primary transmitter rated transmit power, untrusted secondary user initial power, and primary transmitter power allocation ratios. Finally, a large number of simulations show that the time division ratios have a significant impact on the performance of the system, and these simulation results also verify the feasibility and effectiveness of the proposed strategy.